Antibacterial activities of locally used toothpastes against dental pathogens - Tiwari, KB; Shrestha, UT; Acharya, A; Subedi, B; Paudyal, B; KC, U; Agrawal, VP (Journal of Institute of Medicine Nepal, 2009)
Background: Toothpastes need to contain various antimicrobial agents in order to reduce, control and prevent different kinds of dental diseases. Different brands have their own composition and concentration of ingredients for their efficacy. The consumers should aware about the facts associated with their health. Methods: The bacterial pathogens were isolated and identified from various dental samples. Antibacterial activities of 11 different toothpastes available locally in markets were assessed against the isolates by standard agar well diffusion method. Result: Monomicrobial infections were observed in all cases. The bacterial pathogens were found to be Streptococcus mutans, S. salivarius, S. sanguis, S. sobrinus and S. mitis. Of the assayed toothpastes- Colgate Total, Colgate, Anchor White and Pepsodont were found to be highly effective against the pathogens. Conclusion: The result showed that the toothpastes containing Triclosan as a major chemical ingredient posses significant antibacterial activities. Keywords: Streptococcus, Triclosan, Zone-of-inhibition Journal of Institute of Medicine, August, 2008; 30:2 15-18 The full text of this paper is available from the Journal of Institute of Medicine website